Analisis Kinerja Signal Booster 4G LTE 1800 MHz pada Gedung AH Lantai 1 Politeknik Negeri Malang - Wahyu Muhammad Afif; Aisah Aisah; Rachmad Saptono (Politeknik Negeri Malang, 2021)
With the increase in internet users in the current era, especially in office buildings, shopping centers, apartments or other high-rise buildings, the Base Transceiver System (BTS) coverage is not optimal due to the construction of concrete, bricks or steel frames that are dampening the signal. One of the solutions to improve the signal in an Indoor room is Signal Booster. The purpose of this research is to conduct an analysis of the quality of Signal Booster performance in the measurement of walk test and to analyze the potential placement of Signal Booster. The method used is a walk test that aims to determine the value of the received power 4G before and after the installation of Signal Booster. This aims to find out the best layout to be installed by Signal Booster. Based on the results of the research before installing Signal Booster, the room that has the lowest RSRP has an average value of -100dBm to -120dBm. While detelah given a Signal Booster has an average value of -60dBm to 80dBm. This states that Signal Booster can improve the signal quality of the Indoor room